C‐reactive protein to albumin ratio predicts difficult laparoscopic cholecystectomy in patients with acute cholecystitis diagnosed according to the Tokyo Guidelines 2018. Issue 3 (8th February 2022) - Utsumi, Masashi; Sakurai, Yuya; Narusaka, Toru; Tokunaga, Naoyuki; Kitada, Koji; Hamano, Ryosuke; Tsunemitsu, Yousuke; Miyasou, Hideaki; Otsuka, Shinya; Inagaki, Masaru
Abstract: Introduction: Difficult laparoscopic cholecystectomy (DLC) may increase the risk of complications and extend the duration of hospitalization. The aims of this study were to evaluate the predictive value of C‐reactive protein/albumin ratio (CAR) for DLC in patients with acute cholecystitis (AC) diagnosed according to the Tokyo Guidelines 2018 and to develop a preoperative predictive model for DLC. Methods: We retrospectively analyzed 205 patients who had laparoscopic cholecystectomy for AC between January 2012 and December 2020. We defined DLC cases as having one of the following factors: blood loss ≥50 mL, operative time ≥150 minutes, or conversion to open surgery. We classified the remaining cases into the non‐DLC group. Results: Overall, 127 (62.0%) and 78 (38.0%) patients were grouped into the DLC and non‐DLC groups, respectively. Patients in the DLC group had: higher severity grade, which was assessed using the Tokyo Guidelines 2018; higher incidence of postoperative complications; and more hospitalization days than those in the non‐DLC group. Multivariate analysis revealed that male, CAR (≥3.20), and pericholecystic fat hyperdensity on computed tomography (CT) were independent predictors of DLC. We developed a predictive scoring system for DLC based on these three factors (cutoff value, 2.0; area under the curve, 0.75; sensitivity, 71.7%; and specificity, 70.5%). Conclusion: CAR could predict DLC independently in AC patients. We identified male gender, CAR, and pericholecystic fat hyperdensity on CT as predictive factors for DLC and established a preoperative prediction system based on these three factors.